Ultrasound stimulation of the vagal nerve improves acute septic encephalopathy in mice - Imamura, Yukio; Matsumoto, Hisatake; Imamura, Jun; Matsumoto, Naoya; Yamakawa, Kazuma; Yoshikawa, Nao; Murakami, Yuki; Mitani, Satoko; Nakagawa, Junichiro; Yamada, Tomoki; Ogura, Hiroshi; Oda, Jun; et al. (Frontiers in Neuroscience, 2023)
Septic encephalopathy (SE) is characterized by symptoms such as coma, delirium, and cognitive dysfunction, and effective therapeutic interventions for SE remain elusive. In this study, we aimed to investigate the potential alleviating effects of vagal nerve stimulation (VNS) on SE-associated signs. To evaluate our hypothesis, we utilized a mouse model of SE induced by intraperitoneal injection of lipopolysaccharide (0.3mg per mouse) and administered noninvasive, high-frequency ultrasound VNS. To assess the efficacy of ultrasound VNS, we measured inflammation-related molecules, including the α7 nicotinic acetylcholine receptor (α7nAChR) expression in peritoneal macrophages and plasma interleukin 1β (IL-1β) levels. Consistent with our hypothesis, SE mice exhibited reduced α7nAChR expression in macrophages and elevated IL-1β levels in the blood.Remarkably, VNS in SE mice restored α7nAChR expression and IL-1β levels to those observed in control mice. Furthermore, we evaluated the effects of VNS on survival rate, body temperature, and locomotor activity. SE mice subjected to VNS demonstrated a modest, yet significant, improvement in survival rate, recovery from hypothermia, and increased locomotor activity. To investigate the impact on the brain, we examined the hippocampus of SE mice. In control mice, VNS increased the expression of c-fos, a marker of neuronal electrical excitability, in the hippocampus. In SE mice, VNS led to the restoration of aberrant firing patterns in hippocampal neurons. Additionally, proteomic analysis of hippocampal tissue in SE mice revealed abnormal increases in two proteins, tissue factor (TF) and acyl-CoA dehydrogenase family member 9 (ACAD9), which returned to control levels following VNS. Collectively, our findings support the value of exploring the beneficial effects of ultrasound VNS on SE.